Legal and Economic Aspects of Consumer Protection in the Polish and International Futures Market - Wodniak, Krystian Piotr (Journal of Finance and Financial Law, 2017)
The paper presents the legal and economic aspects of consumer protection in the Polish and international futures market and important issues for the extension of this topic. The purpose of the paper is to clarify the issue of supervision and reflections on the possibility of informing the consumer on the Polish futures market and illustrating how legal and economic protection looks in the EU and in the world. Also discussed is the general relationship between the client and the investment entities (Polish and foreign) and how such relationships affect the clarity of the futures market.